SISTEM INFORMASI PENERIMAAN PESERTA DIDIK BARU BERBASIS WEBSITE PADA MENLO PARK SCHOOL BY SCHOTERS - Adam Hidayat, (2022)
Technology or web-based communication and information media really needs to be presented in the world of education. Menlo Park School is a formal international standard junior high and high school that is currently registering new students. Menlo Park School is still using several applications in the registration process. This can cause delays in the flow of the registration process and information delivery because they are still using different applications. From these problems, a main forum is needed, namely, a registration information system that contains the registration process starting from providing registration information, filling out forms, checking data, and reporting on the results of the selection in the form of a website application. Making the website will use HTML and PHP. The results of the research on a Design of Information System Registration Web-based at Menlo Park School by Schoters This can simplify and assist all parties involved in the registration process.